Hubungan perilaku merokok dengan kejadian tuberkulosis paru di balai besar kesehatan paru masyarakat (bbkpm) surakarta - Falletehan, Ryan Arvisza; , dr. Niwan Tristanto Martika, Sp. P; , dr. Ilma Rizkia Rahma (2014)
Pulmonary Tuberculosis (pulmonary TB) is a disease that is a problem at the level of the world, including Indonesia. Given the high number of deaths caused by pulmonary tuberculosis. Smoking increases the risk of pulmonary tuberculosis infection 3.1 times. Research Objectives. This study aims to determine the relationship of smoking to the incidence of pulmonary tuberculosis in Besar Kesehatan Paru Masyarakat (BBKPM) Surakarta. Methods. This study use observational study with cross sectional approach. Taken 35 sample with pulmonary tuberculosis and 35 not pulmonary TB with purposive and consecutive sampling technique. The statistical test used is Chisquare. Results. Patients with pulmonary tuberculosis were found more smokers (25.7%), whereas non-pulmonary TB is more common among non-smokers (30.0%). The results of statistical tests between smoking behavior with the incidence of pulmonary tuberculosis with Chi square, p-value = 0.027, means there is a significant relationship. Conclusion. Based on the research results, it can be concluded there is a relationship. The relationship is difference in the numbers of smoking behavior and pulmonary TB incidence at BBKPM Surakarta where the incidence of pulmonary tuberculosis was higher is smokers (25.7%). Keywords. Smoking behavior, Pulmonary Tuberculosis.